Nurse capacity building strategy in health services in hospitals - Suprapto, Suprapto; Rifdan, Rifdan; Gani, Hamsu Abdul (Linguistics and Culture Review, 2021)
Nurses are at the forefront of health services and even have a major influence in determining the degree of quality of health services in hospitals. So that the knowledge, skills and attitudes of nurses need to be improved, especially in the professional aspects of health service delivery. The purpose of this study was to describe and analyze the capacity building of nurses in health services in hospitals. Method; this research is qualitative with a case study approach. The focus of the research is the extent to which the steps of the nurse capacity building process in health services in hospitals. The instrument used in this study was the researcher himself. Data collection by interview, observation and literature review. Data analysis using; condensing data, presenting data, and drawing conclusions or verification. The results showed that the capacity-building process carried out by the hospital had gone well, but it needed to be improved in terms of spiritual and technological abilities for nurses so that it would improve the quality of health services. Conclusion; that in improving health services, capacity building for nurses is needed by adding the concept of a spiritual and technological approach.